Evaluating Disease Threats to Sustainable Poultry Production in Africa: Newcastle Disease, Infectious Bursal Disease, and Avian Infectious Bronchitis in Commercial Poultry Flocks in Kano and Oyo States, Nigeria - Ekiri, Abel B.; Armson, Bryony; Adebowale, Kehinde; Endacott, Isabella; Galipo, Erika; Alafiatayo, Ruth; Horton, Daniel L.; Ogwuche, Adah; Bankole, Olorunsola N.; Galal, Hussein M.; Maikai, Beatty-Viv; Dineva, Mariana; et al. (Frontiers in Veterinary Science, 2021)
The growth of the poultry industry in Nigeria is constrained by major poultry diseases, despite the implementation of vaccination programs. This study aimed to assess the level of protection against Newcastle disease (ND), infectious bursal disease (IBD) and avian infectious bronchitis (IB) afforded by current vaccination schedules and characterise the circulating virus strains in commercial poultry flocks in Nigeria. A cross-sectional study was conducted on 44 commercial poultry farms in Oyo and Kano states of Nigeria. Serum and tissue samples and data on flock, clinical and vaccination history were collected on each farm. Farms were classified as being protected or not protected against ND, IBD and IB based on a defined criterion. Real-time reverse transcription polymerase chain reaction (RT-PCR) testing was performed for each target virus on tissue samples and positive samples were sequenced. A total of 15/44 (34.1%), 35/44 (79.5%) and 1/44 (2.3%) farms were considered to be protected against ND, IBD and IB, respectively, at the time of sampling. NDV RNA was detected on 7/44 (15.9%) farms and sequences obtained from 3/7 farms were characterised as the lentogenic strain. IBDV RNA was detected on 16/44 (36.4%) farms tested; very virulent (vv) IBDV and nonvirulent (nv) IBDV strains were both detected in 3/16 (18.8%) positive samples. Sequences of IBDV isolates were either clustered with a group of genotype 3 virulent IBDV strains or were related to vaccine strains MB and D78 strains. IBV RNA was detected on 36/44 (81.8%) farms, with variant02, Massachusetts, 4/91 and Q1 variants detected. Sequences of IBV isolates were either clustered with the vaccines strains Massachusetts M41 and H120 or were most closely related to the D274-like strains or a clade of sequences reported in Nigeria and Niger in 2006 and 2007. This study revealed that most study farms in Oyo and Kano states did not have adequate protective antibody titres against IBV and NDV and were therefore at risk of field challenge. IBDV and IBV RNA were detected on farms with a history of vaccination suggesting potential vaccination failure, or that vaccine strains used may not be protective due to mismatch with circulating strains.